Mixed Methods Research Design: Integrating Qualitative and Quantitative Approaches in Social Science Inquiry - Dr. Syed Usman Shahid; Dr. Taha Shabbir; Meritorious Prof. (Retd) Dr. Nasreen Aslam Shah (Journal of Social Signs Review, 2026)
Mixed methods research (MMR) has emerged over the past four decades as a distinct and increasingly influential methodological paradigm in the social, health, educational, and applied sciences, offering researchers a systematic framework for integrating qualitative and quantitative approaches within a single study or coordinated program of inquiry. This paper provides a comprehensive, critically informed, and practically oriented methodological review of mixed methods research design, tracing its intellectual development from Campbell and Fiske's (1959) multi-trait multi-method matrix and Denzin's (1978) triangulation typology through the paradigm debates of the 1980s, the emergence of formal design typologies in the 1990s, and the consolidation of MMR as a third methodological paradigm by Tashakkori and Teddlie (2003) and Creswell and Plano Clark (2007, 2018). The paper systematically addresses the philosophical foundations of MMR across pragmatism, dialectical pluralism, transformative, and critical realist positions; a comprehensive typology of six major designs explanatory sequential, exploratory sequential, convergent parallel, embedded, transformative, and multiphase with their notation conventions, priority structures, and appropriate research contexts; the critical concept of integration and its four principal strategies; quality criteria specific to mixed methods including legitimation, inference quality, and integration rigour; ethical challenges involving dual-consent, community participation, and reporting obligations; disciplinary applications across health, education, policy, and media research; and a systematic comparison with mono-method qualitative and quantitative approaches. Six structured tables consolidate historical, typological, procedural, philosophical, comparative, and quality information. Recent developments including complexity-adaptive designs, participatory MMR, the use of natural language processing and machine learning as analytical strands within mixed methods frameworks, and the emerging field of mixed methods synthesis are addressed critically. The paper argues that MMR's most important contribution to social science inquiry is not the mere combination of data types but the capacity for meta-inference: the production of conclusions that transcend what either strand alone could produce and that are grounded simultaneously in the breadth of quantitative evidence and the depth of qualitative understanding. Keywords: Mixed methods research, research design, qualitative research, quantitative research, triangulation, integration, pragmatism, sequential design, convergent design, meta-inference